Association of Average Telomere Length with Body-Mass Index and Vitamin D Status in Juvenile Population with Type 1 Diabetes - TESOVNIK, Tine (Zdr Varst, 2015)
BACKGROUND: Type 1 diabetes (T1D) is an autoimmune chronic disease where hyperglycemia, increased risk of oxidative stress, advanced glycation end-products and other genetic and environmental factors lead to T1D complications. Shorter telomeres are associated with hyperglycemic levels and lower serum vitamin D levels. METHODS: Average telomere length (ATL) in whole blood DNA samples was assessed with qPCR method in 53 Slovenian T1D children/adolescents (median age 8.7 years, 1:1.3 male/female ratio). Body mass index standard deviation score (BMI-SDS), glycated haemoglobin and serum level of vitamin D metabolite (25-(OH)-D3) and the age at the onset of T1D were collected from the available medical documentation. RESULTS: Results indicate shorter ATL in subjects with higher BMI-SDS when compared to those with longer ATL (0.455 ± 0.438, −0.63 ± 0.295; p=0.049). Subjects with higher BMI-SDS had lower serum vitamin D levels when compared to those with lower BMI-SDS (40.66 ± 3.07 vs. 52.86 ± 4.85 nmol/L; p=0.045). Vitamin D serum levels did not significantly differ between subjects with longer/shorter ATL. CONCLUSION: T1D children/adolescents with shorter ATL tend to have higher BMI-SDS. Lower serum vitamin D levels were associated with higher BMI-SDS, while associations between vitamin D serum levels, age at the onset of T1D, glycated haemoglobin and ATL were not observed. Additional studies with more participants are required to clarify the role of the telomere dynamics in T1D aetiology and development of complications.